Acupuncture and manual therapy for rotator cuff tears: A protocol for systematic review and meta analysis. Issue 21 (22nd May 2020) - Tang, Hongzhi; Luo, Fei; Fan, Huaying; Huang, Li; Liao, Shichuan; Yu, Wenjing; Chen, Yunbei; Qin, Xuefei; Chen, Jiao
Abstract: Background: The tears of rotator cuff is caused by the tears or aseptic inflammation of tendon tissue such as subscapular muscle, supraspinatus muscle, infraspinatus muscle, teres minor muscle, and so on, which make up the rotator cuff. Managements of rotator cuff disease often include acupuncture and manual therapy, usually delivered together. The aim of this review is to assess the effectiveness and safety of such interventions in patients with pain and dysfunction caused by rotator cuff tears. Methods: We will search the EMBASE, the Cochrane Library, Ovid MEDLINE, PubMed, Web of Science, Chinese Biomedical Literature Database, Chinese National Knowledge Infrastructure, Wanfang Database, the Chongqing VIP, the US National Institute of Health, the NIH clinical registry Clinical Trials, the International Clinical Trials Registry Platform, the Australian New Zealand Clinical Trials Registry and the Chinese clinical registry, from their inception to April 1, 2020. Randomized controlled trials that include patients with rotator cuff tears receiving acupuncture and manual therapy versus a control group will be included. The selection of studies, data extraction and risk of bias assessment will be conducted by 2 independent researchers. A third review author will resolve disagreements. The dichotomous data will be presented as risk ratios with 95% CIs and the continuous data will be presented as weighted mean differences or standardized mean differences with 95% CIs. Evidence quality will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation system. Discussion: This systematic review will provide updated evidence of various types of acupuncture and manual therapy specifically focuses on its effectiveness and safety for patients' pain and dysfunction caused by rotator cuff tears. Ethics and dissemination: Ethical approval is not necessary as this review will not require data from individual patients. The results of this will be published through peer-reviewed journal articles or conference presentations. Registration: Open Science Framework Preregistration. Registration number 10.17605/OSF.IO/M3NKV. Abstract : Supplemental Digital Content is available in the text